2018
DOI: 10.3390/nano8060370
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic Solid Based on Single-Walled Carbon Nanohorns: Preparation, Characterization, and Practical Evaluation as a Sorbent

Abstract: A monolithic solid based solely on single walled carbon nanohorns (SWNHs) was prepared without the need of radical initiators or gelators. The procedure involves the preparation of a wet jelly-like system of pristine SWNHs followed by slow drying (48 h) at 25 °C. As a result, a robust and stable porous network was formed due to the interaction between SWNHs not only via π-π and van der Waals interactions, but also via the formation of carbon bonds similar to those observed within dahlia aggregates. Pristine SW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…As shown in the SEM image (Figure S1a, Supporting Information), the pristine CNH gathered into spherical shapes under the action of the van der Waals force. [ 19 ] From the TEM image of the pristine CNH (Figure S1b, Supporting Information), it can be observed that the diameter of the CNH aggregates is ≈50–100 nm, and they are mainly dahlia‐type CNH. [ 20 ] The angular structure of the CNH is evident from the high‐resolution TEM image (Figure S1c, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in the SEM image (Figure S1a, Supporting Information), the pristine CNH gathered into spherical shapes under the action of the van der Waals force. [ 19 ] From the TEM image of the pristine CNH (Figure S1b, Supporting Information), it can be observed that the diameter of the CNH aggregates is ≈50–100 nm, and they are mainly dahlia‐type CNH. [ 20 ] The angular structure of the CNH is evident from the high‐resolution TEM image (Figure S1c, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…(Padua, Italy) and present a dahlia-type shape with a diameter of 60-120 nm. Electron microscopy evidence of the structure and morphology of the CNHs used in this work can be found in the literature [24][25][26].…”
Section: Methodsmentioning
confidence: 99%
“…1[A]). 7,55,56 Variations in the pressure of the carrier gas in the synthesis chamber might be responsible for the mixed morphologies of the aggregates. 7 The mean lateral sizes of the bud-like and dahlia-like aggregates were calculated as 46.0 AE 16.6 nm (number = 29) and 79.5 AE 12.1 nm (number = 31), respectively, as shown in the histogram (Fig.…”
Section: Morphology and Crystallography Of O-swcnhsmentioning
confidence: 99%